STRUCTURE DEVELOPMENT AND FORMING MECHANISM OF DEEP WATER THRUST FOLDS BELT, SOUTHERN PART OF NORTH MAKASSAR BASIN, MAKAS SAR STRAIT. - Hidayat, Andry
The Forming of Makassar Strait and Sulawesi Island involves the interaction of several microcontinents results of fragment of plate tectonics. Makassar Strait geologically divided into two sedimentary basins, North Makassar Basin and South Makassar Basin. Both basins are separated by Adang strike-slip (NW-SE trend) faults which are located in the northern part of Paternoster high. Deep Water Thrust Folds Belt (DWTFB) is part of the West Sulawesi Folds Belt (WSFB) are only formed on the northern part of Adang fault and within North Makassar Basin. In the South Makassar Basin there is no existing of deep water thrust folds belt. DWTFB could be seen into seabed with water depth up to 2500 meters. This indicates that the deformation process still active and continue until present day. The study was conducted to determine the characteristics and mechanism of DWTFB in the Southern part of North Makassar Basin, the border between the North Makassar Basin and South Makassar Basin. In order to answer the purpose of the study, the main data used is 2D seismic data that has been reprocessed. In addition regional tectonic framework is obtained from several studies and publications are used as supporting data. The method used in this study following: cross-section of the time structure analysis, time structure map, correlation of thrust fault structure, and tectonic modeling based on reconstruction of tectonic phase that occurs from time to time. Interpretation of cross section time shows that DWTFB in the Southern part of North Makassar Basin can be divided into two areas of deformation, which are North Deformation Region and South Deformation Region. Both areas are separated by sinistral strike-slip faults. Northern Deformation Region is characterized by folds associated with thrust fault and many folds are formed to the westward (Borneo). Thrust Fault formed above the ramp with Fault Propagation Fold type is developed. There are two areas of ramp; it called Major ramp and Minor ramp. vi Southern Deformation Region is characterized by several folds are formed it’s not as much as the North Deformation Region. This is due to the narrowing of Makassar Strait by Paternoster high and Sulawesi Island. Based on the characteristics of the folds formed in the study area and the appearance of folds until seabed, the forming mechanism of folds belt involve active tectonic until present day. Microcontinent of West Sulawesi or Microcontinent Makassar is an active tectonic to the formation of DWTFB in the North Makassar Basin. The presence of Adang strike-slip is barrier the formations of DWTFB only occur in the North Makassar Basin. Status changes from strike-slip Fault with transform mechanism and movement direction is dextral strike-slip fault into sinistral strike-slip fault occurred during the Pliocene time.